2014
DOI: 10.1007/s11071-014-1793-3
|View full text |Cite
|
Sign up to set email alerts
|

The improved results with Mathematica and effects of external uncertainty and disturbances on synchronization using a robust adaptive sliding mode controller: a comparative study

Abstract: In this computational article, the improved results when different chaotic systems are synchronized using robust adaptive sliding mode controller (RASMC) has been presented in which the simulation is based on Mathematica as well as the effects of external uncertainties (EU) and external disturbances (ED) have been studied in the synchronization of two different chaotic systems. For the same pairs (master and slave systems) of considered chaotic systems (Lorenz, Chen and Liu) and implemented technique (RASMC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…There are innumerable robust techniques have been developed based on the advantages over predecessor one in terms of stability, time response, low chattering, effects of modeling uncertainty and noise. 18,19 There can also be seen innumerable researches based on the systems like synchronization of identical/non-identical systems, different orders (called as Reduced/Increased order), and integer/fractional. [20][21][22][23][24] Numerous worthy researches have also been investigated based on applications of synchronization including security through multi-switching, compound, combination-combination synchronization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are innumerable robust techniques have been developed based on the advantages over predecessor one in terms of stability, time response, low chattering, effects of modeling uncertainty and noise. 18,19 There can also be seen innumerable researches based on the systems like synchronization of identical/non-identical systems, different orders (called as Reduced/Increased order), and integer/fractional. [20][21][22][23][24] Numerous worthy researches have also been investigated based on applications of synchronization including security through multi-switching, compound, combination-combination synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…for identical, non‐identical, integer, fractional systems with and without the effects of modeled uncertainty and noise. There are innumerable robust techniques have been developed based on the advantages over predecessor one in terms of stability, time response, low chattering, effects of modeling uncertainty and noise 18,19 . There can also be seen innumerable researches based on the systems like synchronization of identical/non‐identical systems, different orders (called as Reduced/Increased order), and integer/fractional 20–24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For demonstration purposes, circular restricted threebody problem and the Lorenz system were used as a master and slave system, respectively. Shahzad [24] has investigated the improved results with Mathematica and further studied the effects of external uncertainty and disturbances on stability using adaptive sliding mode control. It has been seen that the synchronization of chaotic systems with unknown parameters is an issue.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of Shahzad [23] focused the attention of researchers on how to choose a model based synchronization technique and the appropriate mathematical tools for simulation. Pourmahmood et al [24] have developed a Robust Adaptive Sliding Mode Control (RASMC) and implemented it successfully on three well known chaotic systems (Lorenz, Chen and Liu) using MATLAB for all of the simulations, but when the same study was done using Mathematica by Shahzad [23], remarkable changes were observed in terms of time response to stabilize the synchronization.…”
Section: Introductionmentioning
confidence: 99%